2022
DOI: 10.1186/s12933-022-01631-4
|View full text |Cite
|
Sign up to set email alerts
|

Real-world characteristics, modern antidiabetic treatment patterns, and comorbidities of patients with type 2 diabetes in central and Eastern Europe: retrospective cross-sectional and longitudinal evaluations in the CORDIALLY® study

Abstract: Background Guidelines from 2016 onwards recommend early use of SGLT2i or GLP-1 RA for patients with type 2 diabetes (T2D) and cardiovascular disease (CVD), to reduce CV events and mortality. Many eligible patients are not treated accordingly, although data are lacking for Central and Eastern Europe (CEE). Methods The CORDIALLY non-interventional study evaluated the real-world characteristics, modern antidiabetic treatment patterns, and the prevalen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Cardiovascular disease is one of the most important diabetes-related complications [ 1 – 3 ]. Rubler et al identified diffused myocardial fibrosis, cardiac hypertrophy, and myocardial microangiopathy in diabetes patients and termed it diabetic cardiomyopathy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cardiovascular disease is one of the most important diabetes-related complications [ 1 – 3 ]. Rubler et al identified diffused myocardial fibrosis, cardiac hypertrophy, and myocardial microangiopathy in diabetes patients and termed it diabetic cardiomyopathy [ 4 ].…”
Section: Introductionmentioning
confidence: 99%